B81 Bone Vibrator-Induced Vestibular-Evoked Myogenic Potentials: Normal Values and the Effect of Age - Zhang, Yuzhong; Chen, Zichen; Zhao, Huandi; Shen, Jiali; Zhong, Bo; Wu, Qiong; Yang, Jun; Jin, Yulian; Zhang, Qing; Ren, Pengyu (Frontiers in Neurology, 2022)
Objective To define the normal values and examine the influence of aging on B81 bone vibrator-induced cervical vestibular-evoked myogenic potentials (B81-cVEMPs) and ocular vestibular-evoked myogenic potentials (B81-oVEMPs). Methods Seventy healthy subjects, divided into seven groups according to their ages, were enrolled in this study. The 4–9-, 10–19-, 20–29-, 30–39-, 40–49-, 50–59-, and 60–70-year-old participants were divided into groups I–VII, respectively. B81-cVEMP and B81-oVEMP were recorded in each group. Results The B81-cVEMP response rates for groups I–VII were 100, 100, 100, 100, 95, 95, and 75%, respectively, with significant differences only between groups I–VI and group VII (p = 0.047, p < 0.05). The B81-oVEMP response rates for groups I–VII were 100, 100, 100, 100, 70, 65, and 40%, respectively, with significant differences only between groups I–IV and groups V–VII (p = 0.020, p = 0.008, p = 0.000; p < 0.05). The threshold, P13, and N23 latencies of B81-cVEMP positively correlated with age (r = 0.756, p = 0.000; r = 0.357, p = 0.003; r = 0.316, p = 0.009; p < 0.05). The raw amplitudes and corrected amplitudes negatively correlated with age (r = −0.641, p = 0.000; r = −0.609, p = 0.000, p < 0.05). For B81-oVEMP, the corrected amplitudes negatively correlated with age (r = −0.638, p = 0.000, p<0.05), but the threshold and N10 latency positively correlated with age (r = 0.768, p = 0.000; r = 0.334, p = 0.009, p < 0.05). Moreover, the interaural asymmetry ratio did not significantly correlate with age for B81-cVEMP and B81-oVEMP. Conclusion As age increased, the B81-cVEMP response rate decreased, the thresholds increased, P13 and N23 latencies were prolonged, and the raw amplitude and corrected amplitude decreased. The B81-oVEMP response rate and corrected amplitude decreased, the thresholds increased, and N10 latency was prolonged with age. These changes are probably due to the occurrence of morphological and functional changes in the vestibular system with aging. Therefore, we suggest establishing different reference values according to different age groups when evaluating the VEMP results in patients with vestibular diseases.